If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying gs + 5 = 16 Reorder the terms: 5 + gs = 16 Solving 5 + gs = 16 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + gs = 16 + -5 Combine like terms: 5 + -5 = 0 0 + gs = 16 + -5 gs = 16 + -5 Combine like terms: 16 + -5 = 11 gs = 11 Divide each side by 's'. g = 11s-1 Simplifying g = 11s-1
| 6[n-4]=3n | | 6+1x=3 | | 7+6(-6a+7)=-167 | | (2x+7)(5x+2)(x-4)=180 | | 8-2x=-1 | | 7d^4=35d^3 | | 6(7a+4)-4a=100 | | -3x^6= | | 32=35x | | 2x+6-6x+13=26x-45 | | 2.5x^2-2=3 | | x-.06x=24.44 | | 50+0.10m=45+0.30m | | 9m^2+15m+25= | | 48x-24+48-9x=24x+56 | | -4.8(x-3.25)=14.4 | | -4(5y+3)+5(1+4y)=0 | | 15+0.35x=30+0.30x | | 8x-24+4x=-19 | | -10+9p=44 | | (3x+3)(X+3)=-1 | | ln(8x^5)=ln(5x)+3 | | 9(5+v)=-90 | | -4=-9+w | | -100+(-77)= | | 2x+x+4x= | | F(x)=x^4-4x^3+16 | | -12x^2+19x-22=0 | | 63-2x=70 | | 30=x-.25x | | -3x-5x=2x+10 | | -25x+25=75 |